A new prediction method for multi-crack initiation of anisotropic rock. (April 2022) - Sun, Dongliang; Rao, Qiuhua; Wang, Shanyong; Yi, Wei; Zhao, Chenchen
Highlight: A new multi-crack initiation criterion of anisotropic rock is established. Effects of crack relative positions and sedimentary angle on maximum SIF ratio is studied. Two collinear cracks are always initiated at inner-tips in Mode I (α1  ≥ 28°) or in Mode II (α1  < 28°). Mode II fracture occurs only when the two cracks both have small inclination angles. The new criterion is verified by uniaxial compression tests of double-cracked shale specimens. Abstract: Multi-crack initiation prediction of anisotropic rock is very important for designing fracture-networks and improving efficiency of shale-gas exploitation. Current literature is mainly focused on multi-crack interacting stress intense factors (SIFs) but less on multi-crack initiation criterion for anisotropic rock. In this study, a new multi-crack initiation criterion of anisotropic rock is established based on the maximum ratio of Mode I and Mode II SIF to its fracture toughness on the critical crack plane ( θIC or θIIC ), K I M θ IC / K IC M θ IC and K II M θ IIC / K IIC M θ IIC, in order to predict the multi-crack initiation parameters (crack initiation tip, angle and mode). Effects of crack relative position ( α1, γ, D h and D s ) and sedimentary angle (β) on K I M θ IC / K IC M θ IC and K II M θ IIC / K IIC M θ IIC are analyzed for anisotropic rock. Research results show that under uniaxial compression stress, two collinear cracks are always initiated at two inner-tips simultaneously in Mode I (with large crack incline angle, e.g., α1  ≥ 28°) or in Mode II (with small crack incline angle, e.g., α1  < 28°). Two vertical cracks (α1  = 45°, α2  = 135°, with extension line of one crack passing through the center of another crack) are initiated at only one crack-tip for any sedimentary plane angle (β = 0°∼180°) in Mode I. Two arbitrary cracks are initiated at one crack-tip in Mode II only when the absolute value of two-crack incline angles with respect to horizontal direction are both small (e.g., |α1 |=10°<28°, |α2 |=20°<28°). Theoretical prediction results are in good agreement with uniaxial-compression test results of shale and sandstone plates with two arbitrary cracks. The new multi-crack initiation criterion can be further developed to predict the whole multi-crack propagation process of anisotropic rock. It provides a theoretical basis for safety assessment of rock engineering and cracking-network formation of shale-gas hydraulic exploitation.